EFEKTIVITAS MEDIA ANIMASI TERHADAP HASIL BELAJAR BIOLOGI SISWA SMPN 2 KEDIRI - Oktarini, Dewi; Jamaluddin, Jamaluddin; Bachtiar, Imam (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2014)
The use of instructional media is essential for understanding Biology. This study aims to determine the effectiveness of the use of animation media on learning outcomes. The study was conducted with quasi-experimental and non-equivalent pre-test-post-test control group designs. Data were taken from the pre-test, post-test and gain scores. The research instrument is a written test in the form of multiple choice questions. Data were analyzed using ’mean difference test’. The results showed that the results of the study on sub photosynthesis and respiration material differed significantly. The gain analysis shows that the animation media has improved student learning outcomes.